Greater Left Inferior Frontal Activation for SVO than VOS during Sentence Comprehension in Kaqchikel - Koizumi, Masatoshi; Kim, Jungho (Frontiers in Psychology, 2016)
Cortical activations during the processing of Kaqchikel transitive sentences with canonical and non-canonical word orders were investigated using functional magnetic resonance imaging. Kaqchikel is an endangered Mayan language spoken in Guatemala. The word order in this language is relatively flexible. We observed higher cortical activations in the left inferior frontal gyrus for sentences with the subject-verb-object (SVO) word order, as compared to sentences with the verb-object-subject (VOS) word order, suggesting that Kaqchikel sentences are easier to process when they have the VOS order than when they have the SVO order. This supports the traditional analysis of Mayan word order: the syntactically simplest word order of transitive sentences in Mayan languages, including Kaqchikel, is VOS. More importantly, the results revealed that the subject-before-object word order preference in sentence comprehension, previously observed in other languages, might not reflect a universal aspect of human languages. Rather, processing preference may be language-specific to some extent, reflecting syntactic differences in individual languages.